Income and education level trajectories and changes in the daily consumption of vegetables after thirteen years of follow-up: the Pró-Saúde Study - Talita Lelis Berti; Diana Barbosa Cunha; Rosely Sichieri; Joana Maia Brandão; Eduardo Faerstein (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: This study aimed to examine whether education level and income trajectories influence vegetable consumption changes over 13 years among civil servants at different campuses of a university in the state of Rio de Janeiro, Brazil. Methods: Vegetable intake frequency (daily and non-daily consumption), income (per capita), and education level (maintenance of low schooling/ upward mobility/maintenance of high schooling) were assessed at baseline (1999) and in the fourth wave (2011-12) of the Pró-Saúde (Pro-Health) cohort study. A total of 2,381 participants were analyzed. The association between educational and income trajectories and variation in vegetable consumption was assessed via crude and age-adjusted generalized linear models, stratified by sex. Results: Men in upward educational mobility showed a 0.5% increase in vegetable consumption (p=0.01), while women in this group demonstrated a 2.5% increase (p=0.05). Adjusted models showed that women who reduced their income had a lower likelihood of consuming vegetables (odds ratio [OR] 0.93; 95% confidence interval [CI] 0.89-0.97). Conclusions: The findings highlight the influence of social inequalities on vegetable consumption in adults.